THE INTERPRETATIVE ANALYSIS OF THE SPIRITUS DOMINI INTROIT - VÁNYOLOS, András (Studia Universitatis Babes-Bolyai Musica, 2009)
In the glorious days of the Gregorian chant, the melodies were performed by heart; therefore, those who interpreted them had to master a great number of titles, which could suffer small variations at any time. Consequently, the necessity of recording these piece was imminent, a process which was - for the first time in music history - distinctive for every single monastery. This recording method was mainly in reference to the interpretation of such works; the neume recording the gesture of that particular conductor, augmented by certain additional signs. This is a testament of an extremely finely nuanced interpretation, a process that we have chosen to illustrate for you with the help of the Spiritus Domini Introit.